Stability analysis of interconnected discrete-time fractional-order LTI state-space systems - Grzymkowski, Łukasz; Trofimowicz, Damian; Stefański, Tomasz P. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a stability analysis of interconnected discrete-time fractional-order (FO) linear time-invariant (LTI) state-space systems is presented. A new system is formed by interconnecting given FO systems using cascade, feedback, parallel interconnections. The stability requirement for such a system is that all zeros of a non-polynomial characteristic equation must be within the unit circle on the complex z-plane. The obtained theoretical results lead to a numerical test for stability evaluation of interconnected FO systems.
Keywords: stability analysis; discrete-time systems; fractional-order systems